Profil Kompetensi pada Anak Tunanetra Low vision di SLB ABD Negeri Kedungkandang Malang: Pendekatan Sistematis dalam Asesmen - Putri, Ayu Oktaviola Ramadhani; Kadia, Singgi; Wulan, Ameylia Ayu Nawang; Mengga, Ayu Prischa Kathrin; Ummah, Umi Safiul; Harisandi, I GST. Ngurah Putu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to identify the characteristics and competencies of low vision blind children through a comprehensive assessment of functional, academic, and musical arts aspects. The research method uses a qualitative approach with a single case study design on a 4th grade elementary school student at SLB ABD Negeri Kedungkandang Malang. Data collection was carried out through an assessment questionnaire that included visual, intellectual, functional, and artistic aspects. Data analysis was carried out descriptively-qualitatively to produce an in-depth competency profile. The results showed that low vision blind children have remarkable adaptation abilities with complex variations in visual perception. The subjects displayed optimal cognitive abilities, had no difficulty in abstract thinking, were able to read according to their age, and had good communication skills. Functional competencies include braille skills, mobility orientation, and contextual adaptation. The music field shows special potential with superior abilities to imitate tones and express music.